Comparative Models and Images in Mari Folk Songs - Yulia V. Polyakova (Polylinguality and Transcultural Practices)
The work is aimed at studying comparative (structural) models and comparative images (semantic features) of comparisons functioning in Mari folk songs. The structural comparative models in the analyzed texts of calendar-ritual and family-ritual songs are the following: “noun in the nominative case + postposition gaye / gane / gаy / gayak”; “noun in the nominative case + noun in the nominative case”; “noun in the nominative case + postposition semyn / semynak”; “noun in the nominative case + suffix -la ”. In the folk songs of the most productive semantic comparative models in which a person or animal is compared with the object world (the plant object: snege peledysh gaye udyr-tangem kodesh ‘girl-girl, as the flower of strawberry, remains’; zoomorphic object: shyrchyk gae latik unycam ulo ‘I have eleven grandchildren like skvorushka’; natural religious object: vutash petyryme shem ushcalet vud gych lekshe Vudava gae ‘black cow in the stable as the Mother Goddess of the water coming out of the water’; the real object: ‘ chewer muginde gay udyr-tangna kodale ‘as the carrot painted, left our soul-girlfriend’). The comparisons are symbolic in nature, reflect the people’s view of the world, and demonstrate the manifestation of linguistic creativity of speakers of dialect speech. Some comparisons in the works of Mari oral folk art have become symbols, national-specific stereotypes.